Effect of Induced Myopia on the Vestibulo-ocular Reflex Evaluated by Ocular Vestibular Evoked Myogenic Potential - Mazloom , Mahdi; Heravian Shandiz , Javad; Jafarzadeh, Sadegh; Jamali , Jamshid; Momeni-Moghaddam, Hamed (Journal of Ophthalmic and Vision Research, 2024)
Purpose: The possible effects of refractive errors on vestibulo-ocular reflex (VOR) has been a conflicting issue. The aim of this study was to evaluate the effects of induced myopia on VOR using the ocular Vestibular Evoked Myogenic Potential (oVEMP). Methods: In this cross-sectional quasi-experimental study, 35 emmetropic and normal subjects with the mean age of 23.89 ± 3.93 (range, 20–40 years) without any ocular, nervous system, and vestibular disorders, underwent the oVEMP test in the comprehensive rehabilitation center of Mashhad University of Medical Sciences. The oVEMP was performed under five different conditions of testing binocularly, monocularly, and when myopia was induced with the use of spherical lenses of +1.00, +3.00, and +5.00 diopters, respectively. There were 2 to 5 min of rest with closed eyes after each condition to avoid adaptation, fatigue, and any other sources of bias. Mean latencies of oVEMP waves (N1 and P1) and amplitudes of N1–P1 complex were measured. Results: There was no significant difference between the right and left sides (P > 0.05). The induced myopia significantly increased the N1 and P1 latencies using lenses of +1.00, +3.00, and +5.00 diopters but the amplitudes of N1–P1 complex were not influenced by the different amounts of induced myopia. There was no significant difference among the different conditions of induced myopia either (P > 0.05). Conclusion: Induced myopia could affect the VOR due to prolonging the latencies of oVEMP waves. However, the amplitudes were not affected and the effects of multiple degrees of induced myopia were not significantly different.